Update – Kalziumstoffwechsel - Schöfl, Christof (DMW - Deutsche Medizinische Wochenschrift, 2019)
A finely balanced control system keeps the extracellular calcium concentration within narrow limits. Disorders of calcium metabolism are often based on altered parathormone levels. Symptoms are not always clear, sometimes they are even missing: the more it is important to know possible associated diseases. The author presents basics, current diagnostics and concrete therapy options. Central hormone for the regulation of the calcium balance is the parathyroid hormone. With decreasing calcium, PTH leads to an increase in extracellular free calcium concentration in three ways. The classic symptoms of pHPT (polyuria, polydipsia, “stone, leg, and stomach pain”) are rare now, as the condition is diagnosed much earlier. Treatment of choice in all symptomatic patients with pHPT is surgery. FHH and pHPT are both characterized by hypercalcaemia and increased parathyroid hormone. The differential diagnosis of urinary calcium excretion, which is usually lower in FHH but normal or elevated in pHPT, is crucial. In primary hypoparathyroidism, parathyroid failure interferes with calcium homeostasis at a central location. Consequences are hypocalcaemia, hyperphosphatemia and lack of active vitamin D. Due to increased urinary calcium excretion, patients with ADH are at high risk for kidney stones, nephrocalcinosis and the development of renal insufficiency. Recently, rhPTH 1-84 has been available for the treatment of hypoparathyroidism. However, long-term data is still lacking to provide a safe indication, considering potential effects and side effects.
Keywords: hormonelles Regelsystem; Kalziumkonzentration; CaSR; FHH; rhPTH1-84